2021
DOI: 10.1186/s12884-021-03657-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial risk factors for postpartum depression in Chinese women: a meta-analysis

Abstract: Background Postpartum depression (PPD) has been identified as a recognized public health problem that may adversely affect mothers, infants, and family units. Recent studies have identified risk factors for PPD in Westerners; however, societal and cultural differences between China and the West could, potentially, lead to differences in risk factors for PPD. No comprehensive study has been conducted to collect all the evidence to provide estimates of psychological and social risk factors in Chi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Therefore, this study suggests that high education may be a protective factor for PND, as other studies have shown [ 69 , 70 ]. But Miyake et al study found no association between maternal education and PND [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study suggests that high education may be a protective factor for PND, as other studies have shown [ 69 , 70 ]. But Miyake et al study found no association between maternal education and PND [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most PPD was the continuation of prenatal psychological problems and emotional disorders, indicating a significant correlation between prenatal psychological status and the occurrence of PPD [ 48 ]. Since the incidence of postpartum depression increases gradually after delivery, the assessment at birth may underestimate the real magnitude of the problem [ 49 ]. Although the second phase of our study (periodical phone calls) could have been useful to detect bonding disorders or late depressive symptoms, our study did not find significant altered scores in depressive or anxiety items.…”
Section: Discussionmentioning
confidence: 99%
“…62 Additionally, it is recognised that PPD is also associated with various psychological, socioeconomic and cultural factors. [63][64][65][66] It is further acknowledged that stressful events like IPV exposure can cause an imbalance between environmental demands and individual resources which may lead to decreased resistance, increased susceptibility to mental health problems and consequently the onset of depression. 67 Not only is IPV a major stressor and a traumatic event that can lead to depression, but it is also known that IPV affects the victim's trust in others, fear, coping styles and levels of isolation which additionally may increase the risk of depression.…”
Section: Open Accessmentioning
confidence: 99%